In vitro and in vivo anti-parasitic activity of curcumin nanoemulsion on Leishmania major (MRHO/IR/75/ER) - Keivan Sahebi; Fatemeh Shahsavani; Fatemeh Mehravar; Gholamreza Hatam; Rasoul Alimi; Amirhossein Radfar; Mohammad Saleh Bahreini; Ali Pouryousef; Aref Teimouri (BMC, 2024)
Abstract The present study aimed to assess the anti-leishmanial effects of curcumin nanoemulsion (CUR-NE) against Leishmania major (MRHO/IR/75/ER) in both in vitro and in vivo experiments. CUR-NE was successfully prepared via the spontaneous emulsification method. The in vitro effect of various concentrations of CUR-NE against L. major promastigotes was assessed using the flow cytometry method. In vivo experiments were carried out in BALB/c mice inoculated subcutaneously with 2 × 106  L. major promastigotes. Mice were treated with topical CUR-NE (2.5 mg/ml), intra-lesion injection of CUR-NE (2.5 mg/ml), topical CUR suspension (CUR-S, 2.5 mg/ml), topical NE without CUR (NE-no CUR), amphotericin B as the positive control group, and infected untreated mice as the negative control group. In vitro exposure of promastigotes to CUR-NE showed a dose-dependent anti-leishmanial effect, with a 67.52 ± 0.35% mortality rate at a concentration of 1250 µg/ml and an IC50 of 643.56 µg/ml. In vivo experiments showed that topical CUR-NE and CUR-S significantly decreased the mean lesion size in mice after four weeks from 4.73 ± 1.28 to 2.78 ± 1.28 mm and 4.45 ± 0.88 to 3.23 ± 0.59 mm, respectively (p = 0.001). Furthermore, CUR-NE significantly decreased the parasite load in treated mice compared with the negative control group (p = 0.001). Results from the current study demonstrated the promising activity of CUR-NE against L. major in both in vitro and in vivo experiments. Moreover, CUR-NE was more efficient than CUR-S in healing and reducing parasite burden in mouse models. Future studies should aim to identify molecular mechanisms as well as the pharmacologic and pharmacokinetic aspects of CUR-NE.